Bijak Bermedia Sosial dengan Memahami Konsekuensi Hukum bagi Generasi Zelenial - Bayu Aji, Alan; Wahyuni, Hesti Ayu (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
This community service activity aims to improve digital literacy and legal understanding among the Zelenial generation through an interactive seminar held at SMA N 1 Ayah, Kebumen, on August 6, 2024. Attended by 74 grade 12 students, this activity emphasized the importance of being wise with social media and understanding the legal consequences of behavior in cyberspace. The first speaker discussed positive behavior on social media, while the second speaker elaborated on the legal consequences of digital violations. Using interactive lectures and case studies, this activity encouraged students to be more thoughtful and responsible in using social media. The active participation of participants in discussions and Q&A showed their increased awareness of ethics and legal risks in social media. This activity is expected to minimize the potential for legal violations and strengthen the digital literacy of the younger generation.